1997
DOI: 10.1203/00006450-199710000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Prostanoid Formation during Feeding of a Preterm Formula with Long-Chain Polyunsaturated Fatty Acids in Healthy Preterm Infants during the First Weeks of Life

Abstract: The objective of this study was to evaluate the effect of conventional and long-chain polyunsaturated fatty acids (LCP)-enriched preterm formula on prostanoid formation in preterm infants during their first weeks of life. In a prospective, randomized, double-blind study, healthy infants received either formula enriched with LCP (n = 10), standard preterm formula (n = 10), or (expressed) breast milk (n = 10). Urine was sampled, and anthropometric measurements were taken at study entry and after the study period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…All trials involved healthy preterm infants fed preterm formula, and 8 of 11 trials had a breast-fed reference group (1,(11)(12)(13)15,(19)(20)(21). Only one (15,16) of these trials reported adequate concealment of allocation, and 9 of 11 trials were either unclear regarding losses to follow-up or failed to follow up ≥20% of infants randomly allocated to treatment groups.…”
Section: Trials Including Lc-pufa In Preterm Infantsmentioning
confidence: 99%
“…All trials involved healthy preterm infants fed preterm formula, and 8 of 11 trials had a breast-fed reference group (1,(11)(12)(13)15,(19)(20)(21). Only one (15,16) of these trials reported adequate concealment of allocation, and 9 of 11 trials were either unclear regarding losses to follow-up or failed to follow up ≥20% of infants randomly allocated to treatment groups.…”
Section: Trials Including Lc-pufa In Preterm Infantsmentioning
confidence: 99%
“…Most recent trials have attempted to add AA with n-3 LC-PUFA to avoid the decline in plasma and erythrocyte AA caused by fish oil supplementation. The five trials [17,19,20,24,25] that added both n-3 and n-6 LC-PUFA reported no adverse effects on growth.…”
Section: Discussionmentioning
confidence: 99%
“…We are aware of 12 RCTs reported in at least 19 separate papers [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. These trials were designed to test the efficacy and safety of varying levels of eicosapentaenoic acid (EPA, C20:5n-3), docosahexaenoic acid (DHA, C22:6n-3) and arachidonic acid (AA, C20:4n-6) in the diets of preterm infants.…”
Section: Trials Involving Lc-pufa In Preterm Infantsmentioning
confidence: 99%
See 2 more Smart Citations